Germ line predisposition variants occur in myelodysplastic syndrome patients of all ages - Feurstein, Simone; Trottier, Amy M.; Estrada-Merly, Noel; Pozsgai, Matthew; McNeely, Kelsey; Drazer, Michael W.; Ruhle, Brian; Sadera, Katharine; Koppayi, Ashwin L.; Scott, Bart L.; Oran, Betul; Nishihori, Taiga; et al. (Blood, 2022)
Abstract - The frequency of pathogenic/likely pathogenic (P/LP) germ line variants in patients with myelodysplastic syndrome (MDS) diagnosed at age 40 years or less is 15% to 20%. However, there are no comprehensive studies assessing the frequency of such variants across the age spectrum. We performed augmented whole-exome sequencing of peripheral blood samples from 404 patients with MDS and their related donors before allogeneic hematopoietic stem cell transplantation. Single-nucleotide and copy number variants in 233 genes were analyzed and interpreted. Germ line status was established by the presence of a variant in the patient and related donor or for those seen previously only as germ line alleles. We identified P/LP germ line variants in 28 of 404 patients with MDS (7%), present within all age deciles. Patients with P/LP variants were more likely to develop higher-grade MDS than those without (43% vs 25%; P = .04). There was no statistically significant difference in outcome parameters between patients with and without a germ line variant, but the analysis was underpowered. P/LP variants in bone marrow failure syndrome genes were found in 5 patients aged less than 40 years, whereas variants in DDX41 (n = 4), telomere biology disorder genes (n = 2), and general tumor predisposition genes (n = 17) were found in patients aged more than 40 years. If presumed germ line variants were included, the yield of P/LP variants would increase to 11%, and by adding suspicious variants of unknown significance, it would rise further to 12%. The high frequency of P/LP germ line variants in our study supports comprehensive germ line genetic testing for all patients with MDS regardless of their age at diagnosis.